Cogan’s Syndrome Combined with Hypertrophic Pachymeningitis: A Case Report - Lu C; Lv P; Zhu X; Han Y (Dove Medical Press, 2024)
Ci Lu,1,* Panpan Lv,2,* Xiaoying Zhu,1 Yongmei Han1 1Department of Rheumatology, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China; 2Department of Ultrasound, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiaoying Zhu; Yongmei Han, Department of Rheumatology, Sir Run Run Shaw Hospital, Zhejiang University School of Medicine, 3# Qingchun East Road, Hangzhou, 310016, People's Republic of China, Email 3202091@zju.edu.cn; 3408235@zju.edu.cnAbstract: Cogan's syndrome (CS) is a rare chronic inflammatory disease, characterized by interstitial keratitis and vestibular auditory dysfunction. Hypertrophic pachymeningitis (HP) is a rare chronic aseptic inflammatory disease of the central nervous system. This article reports a patient with CS coexisting with HP. The patient was a 66-year-old male with fever, headache, red eyes, hearing loss, and significantly elevated inflammatory markers. Cerebrospinal fluid examination, blood culture, and tests for autoantibodies such as antinuclear antibodies were negative. Pure tone audiology (PTA) indicated bilateral sensorineural deafness. Both Positron emission tomography-computed tomography (PET/CT) and vascular color Doppler ultrasound suggest the presence of vasculitis. Considering Cogan's syndrome, the patient received 40 mg of methylprednisolone intravenously once daily. The brain's magnetic resonance imaging (MRI) revealed slightly thickened and enhanced dura mater, suggesting HP. The dose of methylprednisolone was increased to 40 mg intravenously every 8 hours, leading to the patient's improved symptoms and decreased inflammatory markers. Both CS and HP are rare chronic inflammatory diseases, and their coexistence is even rarer, with only two reported cases in literature up to date. The coexistence of CS and HP should be considered when the CS patients with headaches do not respond well to treatment.Keywords: Cogan's syndrome, hypertrophic pachymeningitis, vasculitis